I24 Enriched environment promotes long-term human striatal graft maturation, circuits reconstruction and motor recovery in a rat model of Huntington's disease. (12th September 2022) - Besusso, Dario; Schellino, Roberta; Parolisi, Roberta; Gómez-González, Gabriela; Dallere, Sveva; Scaramuzza, Linda; Ribodino, Marta; Campus, Ilaria; Conforti, Paola; Parmar, Malin; Boido, Marina; Cattaneo, Elena; et al.
Abstract : Background: Huntington Disease (HD) is a monogenetic dominant neurodegenerative disorder that progressively affects motor and cognitive functions as a consequence of the prominent loss of medium spiny projection neurons (MSNs) in the corpus striatum of the basal ganglia1. Human embryonic stem cells (hESCs) may provide novel therapeutic chances to replace deteriorating neurons and restore damaged circuits through cell replacement. Aims: Here, we evaluated the long-term therapeutic potential of hESC-derived striatal progenitors transplanted into the striatum of a quinolinic acid (QA)-based rat model of Huntington's Disease (HD) with the goal of developing effective cell replacement for HD. Methods: To this aim, hESC were differentiated according to an established in vitro differentiation protocol (Delli Carri, Development; 2013) and day 20 progenitors transplanted in the striatum of adult athymic nude rats. The motor performance of the animals was then monitored up to six months of housing in standard and enriched environment (EE) and histological analysis performed at end of observation. Results: Transplanted human striatal progenitors displayed morphological and neurochemical characteristics typical of human medium spiny neurons (MSNs), or interneurons, and they continued to function for up to 6 months following transplantation. Grafts generated domains that resembled discrete ganglionic eminence areas and were wired in both local and long-range striatal circuits and were able to ameliorate QA-affected motor capabilities. Moreover, exposure to EE facilitated host-to-graft connection, increased cell differentiation into the MSN phenotype, and improved task performances. Conclusions: These findings indicate that human striatal progenitor grafts have the ability to mitigate HD signs in the long term, and EE can efficiently hasten the maturation and support the integration of human striatal neurons.